The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/cta.818
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi‐gigabits signal integrity through clock H‐tree

Abstract: The H-tree interconnect network is frequently used for the clock signal sharing in the microelectronic systems. Due to the increase of complexity and operating processing data speed, these interconnect effects can bottleneck the technological advancement. Hence, more accurate interconnect modelling methods are necessary for electronic designers. For this reason, a simple and accurate ultra-wide band (UWB) model of multilevel distributed interconnection clock trees as a single input multiple outputs (SIMO) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…By taking: x=exp()italicjθ the output mesh is propagated by the current i o = i ok through the load resistance R and the Branin sources ( e k , e ok ) which are expressed as: {Ek()=x()ZRIo()Eok()=x[]Ea()()ZiZnIa() …”
Section: Description Of the Kron‐branin Modeling Applied To Symmetricmentioning
confidence: 99%
See 1 more Smart Citation
“…By taking: x=exp()italicjθ the output mesh is propagated by the current i o = i ok through the load resistance R and the Branin sources ( e k , e ok ) which are expressed as: {Ek()=x()ZRIo()Eok()=x[]Ea()()ZiZnIa() …”
Section: Description Of the Kron‐branin Modeling Applied To Symmetricmentioning
confidence: 99%
“…Nevertheless, it was found that the performance of certain clock tree topologies as H‐tree can be limited by the coupling and cross talk effects . So far, most of the developed analytical models of symmetric and asymmetric microstrip interconnect trees are using complex fastidious method using complex calculations of various parameters as Z, Y, and ABCD matrices . The complexity of the analytical calculations limits the model practicability.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of the electrical interconnect structures different phenomena linked to the EMI/EMC effects are occurred [1][2]. These unwanted effects can degrade significantly the operating signal integrity (SI).…”
Section: Introductionmentioning
confidence: 99%
“…These unwanted effects can degrade significantly the operating signal integrity (SI). So, modelling methods have been introduced which must be included during the design process have been developed [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market. Although there are several circuit design objectives to be considered during floorplanning, such as area minimization, wirelength optimization [9], delay reduction [10,11], thermal stability [12][13][14], clock tree synthesis [15] or any combination of these objectives [16][17][18], the basic objective of floorplanning is to minimize the area of the VLSI chip.…”
Section: Introductionmentioning
confidence: 99%